Larval fish dynamics within the coastal nearshore of the Eastern Cape, South Africa - Sotshongaye, Oko (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The coastal nearshore is important for the early development of fishes as it is used for spawning and/or as a nursery. One of the central concerns in coastal ecology is understanding the role of the nearshore for larvae, ultimately providing key knowledge on population dynamics and hence helping in making decisions pertaining to conservation and resource management. The aim of this study was to investigate the alongshore and cross-shore distribution of larval fishes and the links to the physio-chemical conditions (including prevailing winds) and hydrodynamics in the region of Algoa Bay, situated on the south east coast in the warm temperate region of South Africa. Fish larvae were sampled at nine sites for the first component of the study (January 2016 "“March 2017) and at four sites for the second component (November 2019), near the surface and bottom (15-50 m) of the water column as well as at two different distances from shore (~400 m/~3 km) using a set of bongo plankton nets towed behind a boat. Environmental data were simultaneously collected using and acoustic Doppler current profiler (ADCP) and conductivity, temperature, depth (CTD) profiler. Larval fish abundance generally decreased with increasing distance from the shore, however, this varied in space and time, with some larval species recorded in high abundances offshore. Close inshore the larvae of coastal fish species producing benthic eggs (CBE) including the Blenniidae and Gobiesocidae mostly dominated, while offshore the larvae of coastal fish species producing pelagic eggs (CPE) i.e. Sparidae and Cynoglossidae, as well as pelagic fish species producing pelagic eggs (PPE) i.e. Clupeidae and Engraulidae mostly dominated. Vertical distribution of larvae differed according to taxon, with the Callionymidae (CPE), Cynoglossidae and Gobiesocidae occurring at high densities at the bottom of the water column, while the Blenniidae dominated near the surface. Fluorescence, temperature and salinity varied with depth (surface/bottom), being particularly high at the surface; currents moved faster at the surface than the bottom of the water column. Increased abundances of larval fishes were evident after upwelling events (associated with easterly winds) in the Bay, while during downwelling (associated with westerly winds), low densities were generally recorded, except for the sites situated near headlands/capes where there were higher densities of fish larvae during downwelling events. Overall, the results of this study suggest that spawning mode of the adults, oceanography and environmental conditions coupled with what is known of the behaviour of fish larvae, were important in shaping the larval fish community of the Algoa Bay region. These results highlight the importance of incorporating multiple biological (developmental stage, reproductive mode, species) and physical (currents, fluorescence, wind-driven up/down-welling) factors when addressing the mechanims of transport of larval fish in the coastal nearshore.
Keywords: Fishes -- Larvae -- South Africa -- Eastern Cape; Fishes -- Larvae -- Development -- South Africa -- Eastern Cape; Fishes -- Larvae -- Ecology -- South Africa -- Eastern Cape; Coastal ecology -- South Africa -- Eastern Cape; Fishes -- Larvae -- Dispersal -- South Africa -- Eastern Cape